Wet healing and Chinese medicine cupping can be used to form collateral circulation in diabetic foot artery occlusion: a case report - Wu, Shengmei; Peng, Qianqian; Tian, Chunlei; Hu, Junfeng; Wu, Xiandi; Zhang, Lili; Zhang, Jin (Frontiers in Endocrinology, 2025)
This report describes a diabetic patient with a left little toe ulcer who was treated with Wet healing combined with traditional Chinese cupping. This approach successfully improved local blood circulation and facilitated wound healing. This treatment modality provides a new perspective for the comprehensive management of diabetic foot ulcers.